2016
DOI: 10.2298/tsci150701138p
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of nucleate pool boiling heat transfer coefficient under high heat fluxes

Abstract: This paper presents CFD (Computational Fluid Dynamics) approach to prediction of the heat transfer coefficient for nucleate pool boiling under high heat fluxes. Three-dimensional numerical simulations of the atmospheric saturated pool boiling are performed. Mathematical modelling of pool boiling requires a treatment of vapor-liquid two-phase mixture on the macro level, as well as on the micro level, such as bubble growth and departure from the heating surface. Two-phase flow is modelled by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The present paper is an extension of the previous research presented in [15,16]. These papers are related to the numerical prediction of the Critical Heat Flux (CHF) [15] and the comparison of the boiling curve for high heat fluxes close to the CHF [16].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The present paper is an extension of the previous research presented in [15,16]. These papers are related to the numerical prediction of the Critical Heat Flux (CHF) [15] and the comparison of the boiling curve for high heat fluxes close to the CHF [16].…”
Section: Introductionmentioning
confidence: 89%
“…The present paper is an extension of the previous research presented in [15,16]. These papers are related to the numerical prediction of the Critical Heat Flux (CHF) [15] and the comparison of the boiling curve for high heat fluxes close to the CHF [16]. In [15,16] the heat transfer form the heated wall to the boiling two-phase mixture is predicted only at the locations of bubble nucleation, while the convective heat transfer in areas between bubble nucleation sites is neglected.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The control volume based finite difference method is applied for the numerical solution of the set of balance Equations (8)- (10). A pressure-correction equation is derived according to the SIMPLE numerical method [17] from the momentum and mass balance equations.…”
Section: Methodsmentioning
confidence: 99%
“…The use of nanofluid as an alternative of base fluid enhances the heat transfer coefficient applying the Lattice Boltzmann method [14,15]. The computational fluid dynamics (CFD) approach was used to forecast the heat transfer coefficient at a high heat flux [16]. The findings of numerical experiments were compared with calculated values applying empirical correlations and it was suggested that the heat transfer coefficient robustly depends on wall roughness.…”
Section: Of 20mentioning
confidence: 99%